2016
DOI: 10.5271/sjweh.3554
|View full text |Cite
|
Sign up to set email alerts
|

Does exposure to bullying behaviors at the workplace contribute to later suicidal ideation? A three-wave longitudinal study

Abstract: Workplace bullying has been established as a predictor of suicidal ideation, but little is known about the relative impact of different forms of bullying behaviors. This study determines the relative impact of person-related, work-related, and physically intimidating bullying behaviors on subsequent suicidal ideation. Exposure to physical intimidation at work predicted suicidal ideation two years later. Short communication Scand J Work Environ Health. 2016;42(3):246-250. doi:10.5271/sjweh.3554 Does exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 11 publications
(13 reference statements)
2
40
0
2
Order By: Relevance
“…The final column in tables 1 and 2 shows the number of quality indicators present for each study. Only two studies by Nielsen et al 18 30 fulfilled all four indicators of study quality. It should be noted, however, that even these studies only adjusted for basic sociodemographic factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final column in tables 1 and 2 shows the number of quality indicators present for each study. Only two studies by Nielsen et al 18 30 fulfilled all four indicators of study quality. It should be noted, however, that even these studies only adjusted for basic sociodemographic factors.…”
Section: Resultsmentioning
confidence: 99%
“…*Both Nielsen et al 18 30 studies used the same sample. Covariates adjusted for: (a) gender, age, marital status, personality measure of susceptibility to paranoia (reality weakness); (b) gender, age, change in job or workplace; (c) age, gender, baseline SI, shared variance of the indicators of bullying behaviour (person-related, work-related, physically related bullying behaviours); (d) gender, age, occupational skill level, psychosocial job stressors (supervisor support, job control, job demands, job insecurity).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological and psychosomatic reactions become more prominent and severe with persistent exposure. Illustrating these reactions, research shows that prolonged bullying is associated with subsequent reports of anxiety (8,15), depression (8,16), suicidal ideation (17,18), headache (19), and sleep problems (20)(21)(22). In a meta-analysis it was found that exposure to bullying predicted subsequent mental health complaints [odds ratio (OR) 1.68, 95% confidence interval (95% CI) 1.35-2.09] and somatic complaints (OR 1.77, 95% CI 1.41-2.22) after adjusting for baseline health status (9).…”
mentioning
confidence: 99%